Being and Becoming: Addressing Equity, Diversity and Inclusion Issues in Learning Academic Writing through an Academic Integrity Socialisation Process - Khoo, Elaine (Journal of Academic Writing, 2025)
Addressing issues of equity, diversity, and inclusion in academic writing is vital in higher education, especially when considering the lived experiences and education of undergraduates from diverse backgrounds. This paper acknowledges the challenges faced by students unfamiliar with Western academic integrity standards, emphasising the disparities experienced by socioeconomically disadvantaged, racialised, and international students. The paper describes an innovative learner-agentic empowerment approach at a Canadian university designed to enable students from diverse backgrounds to gain the academic, cultural, disciplinary and linguistic capital required to practise academic integrity. Through a mixed-method analysis of 182 undergraduates in a writing support program, we found that students who responded to a reflective prompt on academic integrity at the start of the program wrote substantially more (mean 7050 words) than those who did not respond to the prompt (mean 1692 words) during the month-long program. Qualitative analyses revealed students’ unfamiliarity with cultural differences, academic integrity practices, linguistic challenges, and penalty severity. This model suggests the importance of a proactive, learner-agentic approach to facilitate education about academic integrity and to address equity and inclusivity. The study underscores the importance of systemic pedagogical changes, furthering the dialogue on equity, diversity, and inclusion in higher education.